2020
DOI: 10.1186/s40104-020-00496-5
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid prevents post-weaning diarrhea by improving intestinal barrier integrity and function in weaned piglets

Abstract: Background: Tannic acid (TA) is potential to reduce diarrhea in weaning pigs, but knowledge about the influence of TA on intestinal barrier integrity and function is still scarce. This experiment was conducted to investigate the effects of dietary TA supplementation on growth performance, diarrhea rate, intestinal barrier integrity and function of weaned pigs. Methods: A total of 108 crossbred (Duroc × Landrace × Yorkshire) piglets, with an initial average body weight of 6.60 ± 0.27 kg, were allotted to 3 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 40 publications
6
49
0
Order By: Relevance
“…The decrease in diarrhoea incidence and the positive effect on faecal consistency could be related to the in-feed supplementation of the mixture of functional compounds. These results are in line with other results showing a reduction in diarrhoea related to the inclusion of tannin extracts, leonardite and tributyrin individually supplemented in animal diets, and proposed as a valuable alternative to antibiotics for weaned piglets [28,[55][56][57]. Intestinal integrity supported by tributyrin has been widely demonstrated in the literature, due to the release of three butyric acid molecules in the gut.…”
Section: Serum Metabolic Profilesupporting
confidence: 91%
“…The decrease in diarrhoea incidence and the positive effect on faecal consistency could be related to the in-feed supplementation of the mixture of functional compounds. These results are in line with other results showing a reduction in diarrhoea related to the inclusion of tannin extracts, leonardite and tributyrin individually supplemented in animal diets, and proposed as a valuable alternative to antibiotics for weaned piglets [28,[55][56][57]. Intestinal integrity supported by tributyrin has been widely demonstrated in the literature, due to the release of three butyric acid molecules in the gut.…”
Section: Serum Metabolic Profilesupporting
confidence: 91%
“…Several indices, such as DAO and D-lactate activity, are commonly used to assess intestinal barrier function [ 41 , 42 ]. Some recent studies have demonstrated that polyphenols, such as tannic acid, RES and pterostilbene significantly diminish plasma DAO and D - lactate concentrations [ 12 , 43 ]. Consistent with these observations, our results found that supplementation with RES significantly reduced the levels of plasma DAO and D-lactate in weaned piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea and growth performance Diarrhea is a condition frequently reported in weaned piglets, which severely affects growth performance of piglets and restricts the development of pig farming (15). Enrofloxacin has been regarded as a therapeutic agent for treating diarrhea in weaned pigs, which is not suitable for modern agriculture due to its resistance and residue.…”
Section: Discussionmentioning
confidence: 99%
“…The diarrheal index was based on the fecal consistency scoring system (0, normal; 1, soft feces; 2, mild diarrhea; and 3, severe diarrhea), as described previously. A fecal score of 2 or 3 was considered clinical diarrhea ( 15 ).…”
Section: Methodsmentioning
confidence: 99%